2017
DOI: 10.1016/j.mce.2016.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian transcriptome associated with reproductive senescence in the long-living Ames dwarf mice

Abstract: The aim of the current work was to evaluate the ovarian follicle reserve and the ovarian transcriptome in Ames dwarf (df/df) mice. The results suggest a delayed ovarian aging in df/df mice compared to normal (N) mice. Although a high number of genes were differentially expressed during aging of N mice, only a small fraction of these changed with aging in df/df mice. These alterations involved more than 500 categorized biological processes. The majority of these biological processes, including inflammatory/immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 56 publications
3
22
0
1
Order By: Relevance
“…The PI3K/Akt, FoxO and mTOR signaling pathways are essential for the maintenance of the quiescent stage and initiation of primordial follicle growth [17, 18, 29] and can be regarded as regulators of the rate of ovarian aging. In agreement with that, we have previously observed using the same ovarian RNA samples as the ones employed in the current study for RNASeq transcriptome evaluation and observed that ovarian expression of the Pi3k/Akt pathway is one of the main regulated pathways in df/df mice compared to N mice [20]. In addition, FoxO3a phosphorylation was reduced in primordial follicles of GH-deficient df/df mice [19, 42], suggesting that inhibition of this pathway (insulin/PI3k/Akt/FoxO) is essential for maintenance of primordial follicle quiescence.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The PI3K/Akt, FoxO and mTOR signaling pathways are essential for the maintenance of the quiescent stage and initiation of primordial follicle growth [17, 18, 29] and can be regarded as regulators of the rate of ovarian aging. In agreement with that, we have previously observed using the same ovarian RNA samples as the ones employed in the current study for RNASeq transcriptome evaluation and observed that ovarian expression of the Pi3k/Akt pathway is one of the main regulated pathways in df/df mice compared to N mice [20]. In addition, FoxO3a phosphorylation was reduced in primordial follicles of GH-deficient df/df mice [19, 42], suggesting that inhibition of this pathway (insulin/PI3k/Akt/FoxO) is essential for maintenance of primordial follicle quiescence.…”
Section: Discussionsupporting
confidence: 92%
“…Of these, only three miRNAs were commonly regulated with age between N and df/df mice, indicating a very divergent profile of ovarian miRNAs as both mice genotypes age. It was previously demonstrated that the size of the primordial follicle reserve decreases by approximately 90% from the ages of 0.5 to 1.5 years in N female mice [12], and we demonstrated before that the ovarian reserve of primordial follicles in df/df mice is three times larger than in N mice [19, 20]. Therefore, our finding indicates that changes in the ovarian reserve with aging are reflected in changes in the ovarian miRNA profile of N and df/df mice.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations